Kāma kalā Kamalāmpikā : Kāma kalā vilācam viḷakkattuṭaṉ - Naṭarājaṉ, Es., 1918-1985 (Piratipā Piracuram, 1980)
On the significance of the Kamalāmpikā-Tiyākarāja Temple at Tiruvalur, Thanjavur District, Tamil Nadu; includes hymns to the deity.